Association of the Intronic Polymorphism rs3773364 A>G in Synapsin-2 Gene with Epilepsy Patients in Iraq - Hameedi, Akram Jawad; Saud, Asmaa Mohammed (Iraqi Journal of Science, 2021)
Epilepsy is a central nervous system disease which is characterized by a recurrent seizure that distinguishes it from other similar diseases. Epilepsy may occur due to defects in genes that encode some receptors in the brain. For this reason, this study aimed to understand the association between Synapsin-2 (SYN2) gene and susceptibility to epilepsy. Blood samples were collected from 40 volunteers, including 30 patients suffering epilepsy with an age range of 26-49 years old and 10 healthy individuals with an age range of 25-53 years old. The study sample involved 16 males and 14 females with epilepsy along with 6 males and 4 females healthy subjects. DNA was isolated from the volunteers for PCR-RFLP assay. Genotyping of rs3773364 A>G SYN2 was conducted and the results refer to a highly significant difference in the distribution of AG genotype (P=0.0001), while there is no significant difference in the distribution of AA and GG genotypes, with p values of 0.1702 and 1.00, respectively. The results also showed that gender did not significantly affect the results when comparing patients with the control (p=0.0934). Our findings indicates that SYN2 rs3773364 A>G confers risk to epilepsy and may be implicated in epileptogenesis.